The spoils - Eisenberg, Jesse 1983- (Grove Press, 2015)
"Nobody likes Ben. Ben doesn't even like Ben. He's been kicked out of grad school, lives off his parents' money, and bullies everyone in his life, including his roommate, an earnest Nepalese immigrant. When Ben discovers that his grade school crush is marrying a straitlaced banker, he sets out to destroy their relationship and win her back. The Spoils is a deeply personal and probing comedy written by one of America's most interesting writer-thespians"--Back cover
Description based on print version record
Keywords: Narcissists -- Drama; Immigrants -- Nepal -- Drama; American drama -- 21st century